2000
DOI: 10.1046/j.1365-2095.2000.00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of end-product quality of rainbow trout with finishing diets

Abstract: The effect of dietary lipid level upon various quality parameters of smoked rainbow trout were examined. Fish were fed four experimental diets differing in lipid content (18.8–31.4%). Groups received either a lipid‐rich diet throughout the trial (101 days), a lipid‐rich feed for 46 days followed by a lower fat diet for 55 days and vice versa, or a low fat diet throughout. A fifth group (controls), consisting of commercially reared animals, was employed for comparative purposes. The visceral fraction of experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 28 publications
1
41
0
2
Order By: Relevance
“…The good utilization of the experimental diets by the fish is also mirrored by the absence of significant differences in carcass composition at the end of the experiment. Body lipid stores possibly reflected the fat content of the diets, which was identical in all the experimental diets tested, rather than the protein quality (Haard 1992;Rasmussen et al 2000). FCRs were in line with values reported for grey mullet in the literature (Ravagnan 1992).…”
Section: Discussionsupporting
confidence: 73%
“…The good utilization of the experimental diets by the fish is also mirrored by the absence of significant differences in carcass composition at the end of the experiment. Body lipid stores possibly reflected the fat content of the diets, which was identical in all the experimental diets tested, rather than the protein quality (Haard 1992;Rasmussen et al 2000). FCRs were in line with values reported for grey mullet in the literature (Ravagnan 1992).…”
Section: Discussionsupporting
confidence: 73%
“…In all species, a feed restriction generally causes a decrease in IMF level (Gondret et al, 2000 in rabbits;Rasmussen et al, 2000in fish, Santoso, 2001Pethick et al, 2005 in lambs;Lebret, 2002 and2007 in pigs;Ljubic et al, 2007 in avian species). In rabbits as in other species, energy restriction decreases activities of some lipogenic enzymes without any change in muscle fibre type composition (Gondret et al, 2000), confirming again the idea that IMF is poorly related to fibre types.…”
Section: Manipulating Dietary Protein Energy and Micronutrientsmentioning
confidence: 99%
“…In rabbits as in other species, energy restriction decreases activities of some lipogenic enzymes without any change in muscle fibre type composition (Gondret et al, 2000), confirming again the idea that IMF is poorly related to fibre types. Fasting was also shown to strongly affect both muscle structure and IMF levels in fish so that the current practice to reduce IMF at slaughter is a finishing period of feeding with a low-fat diet that enables to manage IMF without affecting other muscle components (Rasmussen et al, 2000;Rasmussen, 2001).…”
Section: Manipulating Dietary Protein Energy and Micronutrientsmentioning
confidence: 99%
“…At present, the dietary protein content of commercial diet for grass carp is generally 22% in China, such low-protein diets with imbalanced nutrients always induced the mesenteric fat deposition in grass carp compared with the result from high-protein (36-40%) diets. Mesenteric fat (Mustin and Lovell 1993;Rueda et al 2001) and viscera lipid concentration (Rasmussen et al 2000) as well as viscerosomatic index (VSI) (Rasmussen 2001) have been shown to increase with increasing dietary energy. The viscera portion of the fish is discarded as by-product during processing.…”
Section: Introductionmentioning
confidence: 99%